Validation and dyadic invariance of the Infertility Concerns Questionnaire among Brazilian couples - Zaia, Victor; Gremigni, Paola; Casu, Giulia (Frontiers in Psychology, 2025)
IntroductionInfertility often brings profound emotional challenges, intertwining the desire for parenthood with the complexities of communication within and beyond the couple. Existing scales fall short of fully capturing these nuances, prompting the development of the Infertility Concern Questionnaire (ICQ), which uniquely addresses both the parental desire and communication dimensions.MethodsThe ICQ was completed by 350 opposite-sex infertile couples from Brazil, aged 22–58 years, who were undergoing fertility treatment. Both partners of all couples completed the ICQ, and a subsample of 168 couples also completed a measure of infertility-related stress. The factor structure of the ICQ was evaluated using confirmatory factor analysis, and measurement invariance across couple members was tested within a dyadic framework.ResultsConfigural, metric, partial scalar, and strict measurement invariance was supported for the ICQ’s theoretical two-factor model of infertility concerns as made of parental (PAR - Examines the central role that the theme of procreation assumes in the construction of individual identity) and communication (COM - Investigates the significance of interpersonal sharing of reflections and experiences related to the decision to have—or not to have—children) dimensions. No between-partner differences were found in ICQ latent factor means. Reliability was found to be acceptable for both dimensions across genders. PAR correlated positively with intrapersonal infertility-related stress in both males and females, while COM correlated negatively with interpersonal infertility-related stress in females. Significant associations between ICQ scores and type of infertility, history of miscarriage, and treatment failures were observed among females.DiscussionThe findings provide initial evidence of the ICQ’s validity and reliability, suggesting its potential use by professionals in fertility treatment settings to better assess and address the distinct emotional and communicative concerns of individuals and couples experiencing infertility.